Prevalence of Malnutrition and Its Associated Risk Factors Among Children Aged 1-5 Years Admitted in Dr. Jamal Ahmad Rashid pediatric Teaching hospital - Mahmood, Srwsht Wahab; Mohammad, Hayder Fakhir (Journal of Sulaimani Medical College, 2025)
Background and Objectives: Malnutrition continues to pose a major public health challenge for hospitalized pediatric populations, especially in low- and middle-income nations. The present research aimed to assess the rate of malnutrition and to identify the factors contributing to its occurrence among children between the ages of one and five years who were admitted to Dr Jamal Teaching Hospital for Pediatrics. Methods: A cross-sectional study was conducted from December 2024 to March 2025, enrolling 330 children aged 1–5 years. Data were collected using structured questionnaires, anthropometric measurements (weight, height, Body mass index (BMI), Mid upper arm circumference MUAC), and the STRONG kids screening tool. Nutritional status was assessed using WHO growth standards. Logistic regression identified predictors of malnutrition. Results: The mean age of participants was 31.67 ± 16.166 months, with 52.3% males. Anthropometric analysis revealed 18.8% stunting (mild: 16.4%, moderate: 2.4%), 14.8% wasting (mild: 10.6%, moderate: 3.6%, severe: 0.3%), and 13.1% underweight. Notably, 13.7% of children were overweight, reflecting a dual burden. MUAC identified 11.8% with acute malnutrition (moderate: 10.9%, severe: 0.9%). Logistic regression highlighted significant predictors: younger age (OR = 0.978, 95% CI: 0.958–0.999), paternal unemployment (OR = 0.167, 95% CI: 0.060–0.463), housing conditions (owned: OR = 3.041; rented: OR = 3.008), and two daily meals (OR = 2.045, 95% CI: 1.648–5.632). Conclusion: The current study demonstrates a high prevalence of acute malnutrition (wasting) and a significant double burden of undernutrition and overweight among hospitalized children. Key modifiable risk factors include paternal employment, dietary frequency, and housing stability.
Keywords: Prevalence; Risk factors; Malnutrition; admitted children